2020
DOI: 10.3390/ijerph17228448
|View full text |Cite
|
Sign up to set email alerts
|

Sand Flies Control: A Review of the Knowledge of Health Professionals and the Local Community, Province of El Hajeb, Morocco

Abstract: Sand flies are insect vectors of several diseases including leishmaniases. These vector-borne diseases represent a public health problem in several countries around the world, including Morocco. The objective of this study was to assess simultaneously the knowledge of health professionals and inhabitants on sand flies; a cross-sectional survey was conducted between April and June 2019 among 424 people, 34% of whom were health professionals and 66% of whom were inhabitants of the province of El Hajeb in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This is mainly related to the ecology of the parasite rather than to the distribution of the vector [ 30 ]. Thus, recent studies have shown that the sand fly is called “ Chniwla ” by the local population and by health professionals in the region [ 7 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly related to the ecology of the parasite rather than to the distribution of the vector [ 30 ]. Thus, recent studies have shown that the sand fly is called “ Chniwla ” by the local population and by health professionals in the region [ 7 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, this entomological survey around the sand y carried out in the province of El Hajeb in central Morocco has provided both information on the circulating sand y fauna in the region and an opportunity to enrich the Moroccan inventory. The sand y is popularly known by the name "Chniwla" [11,38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vector control is a very important strategic focus for limiting the spread of leishmaniasis. Studies have shown that improving the knowledge of the population and health professionals plays a crucial role in successful vector control activities [11,12]. Also, Qualls et al have shown the effectiveness of attractive sweet baits in controlling sand ies [13] However, the Ministry of Health con rms that vector control in Morocco is mainly based on the monitoring of the sand y population by identifying the localities at risk and with high abundance and the periods of transmission to implement targeted and precise control actions to limit the transmission of the disease to humans and animals [3].…”
Section: Introductionmentioning
confidence: 99%
“…In Morocco, this insect is popularly known as "Chniwla". 20 Relevant research has revealed that the Moroccan population used medicinal plants and traditional preparations based on essential oils to fight the bite of this insect. 21 The use of essential oils and plant extracts as effective insecticides was also proven by pharmaceutical research.…”
Section: Perception and Popular Treatment-seeking Behaviour For Cutan...mentioning
confidence: 99%